2012
DOI: 10.1016/j.vetmic.2012.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for death from canine parvoviral-related disease in Australia

Abstract: Canine parvovirus (CPV) is a highly contagious cause of serious and often fatal disease in dogs worldwide despite the availability of safe and efficacious vaccines. Although a number of studies have focussed on identifying risk factors in disease development, risk factors associated with death from CPV are largely unknown. In this study we analysed a total of 1451 CPV cases reported from an Australian surveillance system - using univariate and multivariate techniques - to determine significant risk factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 27 publications
7
51
0
2
Order By: Relevance
“…Low bodyweight was found to be a significant risk factor for death, even after adjusting for age (Dossin et al 2011). In a recent study, the highest mortality rates were seen in dogs less than 6 months of age, yet this parameter failed to achieve significance (Ling et al 2012). Interestingly, the above study also demonstrated higher case fatality rates in summer compared to other seasons; putatively ascribing it to improved viral particle transmission and increased use of boarding and kennel facilities during the warmer holiday months (Ling et al 2012).…”
Section: Epidemiologymentioning
confidence: 83%
See 2 more Smart Citations
“…Low bodyweight was found to be a significant risk factor for death, even after adjusting for age (Dossin et al 2011). In a recent study, the highest mortality rates were seen in dogs less than 6 months of age, yet this parameter failed to achieve significance (Ling et al 2012). Interestingly, the above study also demonstrated higher case fatality rates in summer compared to other seasons; putatively ascribing it to improved viral particle transmission and increased use of boarding and kennel facilities during the warmer holiday months (Ling et al 2012).…”
Section: Epidemiologymentioning
confidence: 83%
“…In a recent study, the highest mortality rates were seen in dogs less than 6 months of age, yet this parameter failed to achieve significance (Ling et al 2012). Interestingly, the above study also demonstrated higher case fatality rates in summer compared to other seasons; putatively ascribing it to improved viral particle transmission and increased use of boarding and kennel facilities during the warmer holiday months (Ling et al 2012). Data on the seasonality of CPV enteritis is conflicting, most likely owing to different climatic conditions and other varying risk factors in different countries (McCaw and Hoskins 2006, Kalli et al 2010, Pospischil and Yamaho 1987.…”
Section: Epidemiologymentioning
confidence: 92%
See 1 more Smart Citation
“…The clinical manifestations of CPV infection depends on the age and immune status of the dogs, virulence of the virus, dose of the virus and pre-existing or concurrent parasitic, bacterial or virus infections (McAdaragh et al, 1982) Factors that predispose parvovirus infection in puppies are lack of protective immunity, intestinal parasites, overcrowded, unsanitary, and stressful environmental conditions (Hoskins, 1997). It has been stated that Doberman, Rottweiler and German shepherd (GS) dogs seem to be more susceptible to Parvovirus infection than other breed (Ling et al, 2012) Unvaccinated puppies aged between six weeks and six months are at greatest risk of developing CPV related disease (Godsall et al, 2010) The prevalence of canine parvovirus infection was reported as 77-80.4% in Thailand, 82.9% in Korea and 6% in Lithuania (Grigonis et al, 2002). The outbreak of CPV disease in dogs was also reported in Belgium and France (1977), Thailand, USA(1978), Portugal, Pakistan, Italy, Spain, Germany (Lamm and Rezabek, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Parvo virus infection is most commonly manifested by vomiting, haemorrhagic diarrhea and severe leukopenia in dogs of all age, and myocarditis with subsequent heart failure in pups of less than 3 months of age (Nandhi et al, 2010). Pavo viral cases, if untreated, can rapidly progress to severe dehydration, complication by secondary invaders predominantly Escherichia coli which lead to endotoxaemia, septicaemia and disseminated intravascular coagulation (DIC) resulting in a high case fatality (Monika Ling et al, 2012). However, CPV infections have been misdiagnosed, unfortunately due to the symptoms akin to some nematode infections viz., the hook worm infestation which could further negatively influence the recovery in the very young pups due to the prenatal transmission of the larvae (Goddard and Leisewitz, 2010).…”
Section: Introductionmentioning
confidence: 99%